Recent applications of the combination of mesoporous silica nanoparticles with nucleic acids: development of bioresponsive devices, carriers and sensors. (20th January 2017) - Castillo, Rafael R.; Baeza, Alejandro; Vallet-Regí, María
Abstract : The control of many biological roles exerted by nucleic acids turned them into a powerful tool for the development of advanced biotechnological materials when in combination with mesoporous silica nanoparticles. Abstract : The discovery and control of the biological roles mediated by nucleic acids have turned them into a powerful tool for the development of advanced biotechnological materials. Such is the importance of these gene-keeping biomacromolecules that even nanomaterials have succumbed to the claimed benefits of DNA and RNA. Currently, there could be found in the literature a practically intractable number of examples reporting the use of combination of nanoparticles with nucleic acids, so boundaries are demanded. Following this premise, this review will only cover the most recent and powerful strategies developed to exploit the possibilities of nucleic acids as biotechnological materials when in combination with mesoporous silica nanoparticles. The extensive research done on nucleic acids has significantly incremented the technological possibilities for those biomacromolecules, which could be employed in many different applications, where substrate or sequence recognition or modulation of biological pathways due to its coding role in living cells are the most promising. In the present review, the chosen counterpart, mesoporous silica nanoparticles, also with unique properties, became a reference material for drug delivery and biomedical applications due to their high biocompatibility and porous structure suitable for hosting and delivering small molecules. Although most of the reviews dealt with significant advances in the use of nucleic acid and mesoporous silica nanoparticles in biotechnological applications, a rational classification of these new generation hybrid materials is still uncovered. In this review, there will be covered promising strategies for the development of living cell and biological sensors, DNA-based molecular gates with targeting, transfection or silencing properties, which could provide a significant advance in current nanomedicine.